APLIKASI SPOKES-CHARACTERS DALAM KAITAN DENGAN MEREK PRODUK - Widjoyo, Caroline (Institute of Research and Community Outreach - Petra Christian University, 2004)
Advertisement by using spokes-characters have potency to alter the choice of consumer brand with the compared to bigger impact which do not use the spokes-character. A lot of producer which hence spokes-character to increase assess to sell from a product. Spokes-Characters experience of the evolution from time to time keep abreast of the era%2C now emerge the new type of spokes-character and its application. Abstract in Bahasa Indonesia : Iklan dengan spokes-characters berpotensi mengubah pilihan merek konsumen dengan dampak lebih besar dibanding yang tidak menggunakan spokes-character. Banyak produsen yang memakai spokes-character untuk meningkatkan nilai jual dari sebuah produk. Spokes-characters mengalami evolusi dari masa ke masa mengikuti perkembangan jaman%2C sekarang muncul jenis baru spokes-character dan aplikasinya. spokes-characters%2C advertising%2C branding.